Fleming, Tanisha. A ghost story. - Jarvis, Dale Gilbert, 1971- (2011)
Recording of a ghost story told by Tanisha Fleming, a Grade 8 student at Villanova Junior High. Recorded in the Newman Wine Vaults Provincial Historic Site as part of the Young Folklorists Program run by the Heritage Foundation of Newfoundland and Labrador in May, 2011. Tanisha writes that the story, "originated in the late 1500s. I heard it from my teacher in school, Mr. Noseworthy. I picked this story because it was my favourite one he told and I remembered it the most. A girl got married to this guy, she never loved him, only for money. He got sick and passed away. She got remarried, but the guy she was previously married to haunted her, and because of this she died. The husband and two kids stayed in the same house. He heard his name being called at the wharf. When he went there, he was pushed in the water and the two kids were killed in the house. He then moved far away."